2021
DOI: 10.1891/re-20-05
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Intervention Research in Rehabilitation Counseling and Related SettingsFrom 2007 to 2018

Abstract: PurposeRehabilitation counseling has seen many advances in evidence-based practice in the last decade. The purpose of this study was to provide a review of intervention literature conducted within rehabilitation counseling or related fields from the years 2007–2018.MethodA systematic review of rehabilitation research was conducted, and a total of 163 intervention studies were included in the final sample. Description and analysis include a summary of where and when manuscripts were published, aspects of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Many individuals with CID experience challenges and barriers in terms of adjusting to changes in work capacity, career goals, and the work environment after the onset of the disability, or in the process of post-secondary transition. Alternately, career maintenance or employment provides resources (e.g., social, economic, health) that can support and promote psychosocial adaptation (Bishop, 2012;Fetsch et al, 2018;Phillips et al, 2021). It is appropriate therefore that DAC in rehabilitation counseling settings would frequently involve issues of career maintenance and transition.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals with CID experience challenges and barriers in terms of adjusting to changes in work capacity, career goals, and the work environment after the onset of the disability, or in the process of post-secondary transition. Alternately, career maintenance or employment provides resources (e.g., social, economic, health) that can support and promote psychosocial adaptation (Bishop, 2012;Fetsch et al, 2018;Phillips et al, 2021). It is appropriate therefore that DAC in rehabilitation counseling settings would frequently involve issues of career maintenance and transition.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most likely path to seeing an increase in the proportion of dissertations using experimental and quasi-experimental research designs will be from increasing the amount of experimental research conducted by rehabilitation counseling faculty. A recent systematic review of intervention research in rehabilitation counseling suggested that much of the intervention research related to rehabilitation counseling is being conducted outside of traditional rehabilitation counseling programs (Phillips et al, in press). Faculty who are engaged in intervention research are more likely to feel confident steering doctoral students toward and supervising their intervention research.…”
Section: Discussionmentioning
confidence: 99%
“…Vocational counseling interventions have limited recognition for their positive effects, such as improving employability and maintaining a healthier lifestyle, on clients undergoing substance use disorder treatment [12]. Specifically, after completing vocational counseling interventions, consumers are more likely to improve both employment and quality of life [15][16][17][18][19][20] or improve quality of life [20,21].…”
Section: Literature Reviewmentioning
confidence: 99%